A mitochondria-targeting hetero-binuclear Ir(iii)–Pt(ii) complex induces necrosis in cisplatin-resistant tumor cells. Issue 49 (31st May 2018) - Ouyang, Cheng; Chen, Lei; Rees, Thomas W.; Chen, Yu; Liu, Jiankang; Ji, Liangnian; Long, Jiangang; Chao, Hui
Abstract : A hetero-binuclear Ir(iii )–Pt(ii ) complex can selectively accumulate in the mitochondria to induce mitochondrial DNA (mtDNA) damage and evoke cellular events consistent with necrosis in A549R cells. Abstract : A hetero-binuclear Ir(iii )–Pt(ii ) complex was developed as an antitumor agent. In vitro cytotoxicity results indicated that this complex was effective against cisplatin-resistant tumor cells. Mechanism experiments showed that it can overcome cisplatin resistance by increasing cellular uptake, targeting mitochondria, and inducing cell necrosis.